2022
DOI: 10.4103/ijo.ijo_2865_21
|View full text |Cite
|
Sign up to set email alerts
|

Reticular epithelial corneal edema as a novel side-effect of Rho Kinase Inhibitors: An Indian scenario

Abstract: Purpose: To describe clinical course, characteristics, and outcome of reticular epithelial corneal edema (RECE) occurring as a not-so-infrequent adverse effect of a novel drug, Rho-kinase inhibitors (ROCK-I)- netarsudil (0.02%) and ripasudil (0.4%). Methods: This was a retrospective observational non-randomized study. In this study, 12 eyes of 11 patients presenting at a tertiary eye care center between April 2021 and September 2021 were included. All 12 eyes developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previous reports have documented the clinical and OCT findings of honeycomb epithelial oedema. The role of OCT has also been outlined by other authors to differentiate between stromal oedema either occurring due to allograft rejection or because of decompensation 10 11. But none of the earlier reports have described the histopathological findings and this report is the first to do so.…”
Section: Discussionmentioning
confidence: 62%
“…Previous reports have documented the clinical and OCT findings of honeycomb epithelial oedema. The role of OCT has also been outlined by other authors to differentiate between stromal oedema either occurring due to allograft rejection or because of decompensation 10 11. But none of the earlier reports have described the histopathological findings and this report is the first to do so.…”
Section: Discussionmentioning
confidence: 62%
“…A systematic review of 10 studies showed that the most common ocular surface damage caused by Rho kinase inhibitors was conjunctival congestion (19-65%), followed by conjunctival hemorrhage (6-20%) and corneal rotavirus (13-26%) [81]. Bhargava et al also found that netarsudil and ripasudil may result in reticular epithelial corneal edema [82]. However, only 12 eyes were included in this study.…”
Section: Effects Of Rho Kinase Inhibitors On Ocular Surfacementioning
confidence: 86%
“…So far only in case series reticular bullous epithelial edema has been observed with netarsudil use, which resolved after discontinuation. 90 , 91 …”
Section: Rock Inhibitors As Potential Therapeutics For Corneal Diseasesmentioning
confidence: 99%